SKŁADNIKI TOŻSAMOŚCI NARODOWEJ POTOMKÓW POLSKICH PRZESIEDLEŃCÓW Z MAZUR W REPUBLICE CHAKASJI I KRASNOJARSKIM KRAJU FR - Skorwid, Sergiej (Acta Neophilologica, 2018)
The goal of this article is to present the main factors that form Polish national identity or Masurian ethnic peculiarity of the descendants of the Polish immigrants from Masuria who moved at the end of the 19th century to Western Siberia and nowadays live in two villages located in the Krasnoyarsk Krai and in the Republic of Khakassia. The author examines such features as the maintenance of their specific dialect and some elements of the original folk tradition, especially of wedding customs, as well as the collective or individual historical memory which goes back to the roots, but also includes events of different periods of the history of the USSR. Special attention is drawn to the religious factor (conversion from Lutheranism, which was original confession of the Polish immigrants from Masuria, to Baptism).